Air-stable high-rate long-circulation sodium-ion battery positive electrode material as well as preparation method and application thereof
The co-doped tunnel oxide sodium ion battery positive electrode material NaaMn1-x-yTMxTiyO2 was synthesized by the solid phase method, which solved the problems of poor rate performance and insufficient long cycle stability of tunnel manganese-based transition metal oxide positive electrode material, and achieved high rate and long cycle sodium ion battery positive electrode material.
Patent Information
- Application Number
- CN202510188503.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The tunnel-type manganese-based transition metal oxide positive electrode material has problems such as poor rate performance and insufficient long cycle stability during charging and discharging.
A co-doped tunnel oxide sodium ion battery positive electrode material NaaMn1-x-yTMxTiyO2 is synthesized by solid phase method, where TM is one or more of K, Al, Ca, Cu, and Zn. Air-stable high-magnification long-circulating positive electrode material is prepared by ball milling, drying, pressing and high-temperature calcining.
Under the condition of a current density of 24mA/g, the discharge specific capacity of the first round reaches 92.53~104.54mAh/g; the capacity storage rate of 100 cycles with a current density of 120mA/g is 93.1%~98.5%; the capacity retention rate of 1000 cycles for a long time can still reach 90.66%, significantly improving the rate performance and long cycle stability.
Smart Images

Figure CN119890286A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sodium ion battery positive electrode material and a preparation method and application thereof, belonging to the technical field of electrochemistry. Background Art
[0002] In view of the growing demand for environmentally friendly and clean energy in the energy market, traditional lithium-ion secondary batteries have high costs due to the shortage of lithium resources. Sodium, which has similar physical and chemical properties, has the natural advantages of high abundance and low cost. Sodium can replace lithium in the field of large-scale energy storage technology of secondary batteries. Its low price and stable cycle performance have huge commercial value and sustainable development potential.
[0003] The positive electrode material is a key factor limiting the energy density and cycle stability of sodium-ion batteries. The positive electrode materials for sodium-ion batteries currently developed mainly include transition metal oxides, Prussian blue analogs, polyanions and organic materials. Among them, transition metal oxides have attracted much attention due to their high specific capacity and simple production process, becoming the most promising positive electrode materials in sodium-ion batteries. However, they generally have problems such as poor air stability, easy to produce undesirable phase changes during cycling, and low charge and discharge rates, which hinder their practical application in sodium-ion batteries. Compared with layered transition metal oxides, tunnel-type manganese-based transition metal oxide positive electrode materials have good stability in air. However, they have poor rate performance and insufficient long-cycle stability during the charge and discharge process. Therefore, it is of great significance to develop a simple and effective method to improve the rate and long-cycle performance of tunnel-type manganese-based transition metal oxide positive electrode materials. Summary of the invention
[0004] The present invention aims to solve the technical problems of poor rate performance and fast long-cycle capacity decay of existing tunnel-type manganese-based transition metal oxide positive electrode materials, and to provide an air-stable high-rate long-cycle sodium ion battery positive electrode material and its preparation method and application.
[0005] The molecular formula of the air-stable high-rate long-cycle sodium ion battery positive electrode material of the present invention is Na a Mn 1-x- y TM x Ti y O2, where TM is one or more of K, Al, Ca, Cu, Zn, 0.22≤a≤0.66, 0 <x≤0.30,0<y≤0.56。
[0006] The preparation method of the above-mentioned air-stable high-rate long-cycle sodium ion battery positive electrode material is a solid phase method, specifically: according to the positive electrode material Na a Mn 1-x-y TMx Ti y Weigh sodium carbonate, manganese carbonate, the corresponding TM oxide or carbonate, and titanium dioxide, and mix them evenly to obtain a mixture; where Na a Mn 1-x-y TM x Ti y In TM in Ti1−a−x−yNaaMn1−x−yTMxTiyO2, TM is one or more of K, Al, Ca, Cu, Zn, 0.22 ≤ a ≤ 0.66, 0 < x ≤ 0.30, 0 < y ≤ 0.56; then place the mixture in a ball milling jar, add acetone, and ball mill at 200 - 800 r / min for 2 - 24 h to obtain a slurry; then place the slurry in a blast drying oven and dry it at 80 - 150 °C for 1 - 12 h, and then grind it in a mortar for 10 - 60 min to obtain a mixed powder; subsequently, press the mixed powder into a sphere under a pressure of 15 - 25 MPa, place it in a muffle furnace at 800 - 1050 °C and roast it for 8 - 20 h, take it out after natural cooling to room temperature, and grind it into powder to obtain an air-stable high-rate long-cycle sodium-ion battery cathode material. It is a co-doped tunnel-type oxide sodium-ion battery cathode material.
[0007] Furthermore, the amount of acetone added is calculated as 1 - 30 mL of acetone added per 1 - 5 g of powder.
[0008] The application of the above-mentioned air-stable high-rate long-cycle sodium-ion battery cathode material is to use the air-stable high-rate long-cycle sodium-ion battery cathode material to prepare the cathode of a sodium-ion battery. The specific preparation method of the cathode is carried out according to the following steps: Weigh 20% - 95% of the air-stable high-rate long-cycle sodium-ion battery cathode material, 2% - 40% of conductive carbon black, and 3% - 40% of polyvinylidene fluoride by mass percentage; dissolve polyvinylidene fluoride in N-methylpyrrolidone to obtain a colloidal solution; then disperse the air-stable high-rate long-cycle sodium-ion battery cathode material and conductive carbon black in the colloidal solution to obtain a slurry; then coat the slurry on a current collector and dry it to obtain the cathode of the sodium-ion battery.
[0009] Furthermore, on the cathode electrode, the loading of the air-stable high-rate long-cycle sodium-ion battery cathode material is 0.5 - 10 mg / cm 2 . This cathode electrode uses Na a Mn 1-x-y TM x Ti y O2 (where TM = one or more of K, Al, Ca, Cu, Zn, 0.22 ≤ a ≤ 0.66, 0 < x ≤ 0.30, 0 < y ≤ 0.56) as the cathode active material.
[0010] The sodium-ion battery assembled with the positive electrode of the sodium-ion battery consists of a negative electrode, a positive electrode of the sodium-ion battery, a separator, and an electrolyte; wherein the negative electrode is metallic sodium; the electrolyte consists of an organic solvent and a sodium salt; the organic solvent is one or a combination of ethylene carbonate (EC), fluoroethylene carbonate (FEC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and propylene carbonate (PC); the sodium salt is one or a combination of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), sodium fluoride (NaF), and sodium difluoro(oxalato)borate (NaDFOB); the concentration of the sodium salt in the electrolyte is 0.1 mol / L to 10 mol / L.
[0011] Furthermore, the preparation method of the electrolyte is as follows: the sodium salt is heated and dried in a vacuum oven to remove the moisture in the sodium salt; the organic solvent is subjected to vacuum distillation and molecular sieve drying to remove the moisture; then the sodium salt and the organic solvent are fully mixed evenly to obtain the electrolyte.
[0012] The tunnel-type manganese-based transition metal oxide positive electrode material for sodium-ion batteries and its preparation method of the present invention prepare the positive electrode material Na a Mn 1-x-y TM x Ti y O2 (where TM = one or more of K, Al, Ca, Cu, Zn, 0.22 ≤ a ≤ 0.66, 0 < x ≤ 0.30, 0 < y ≤ 0.56). The sodium-ion battery prepared using the positive electrode material provided by the present invention has an initial discharge specific capacity of 92.53 to 104.54 mAh / g under the condition of a current density of 24 mA / g, a capacity retention rate of 93.1% to 98.5% after 100 cycles under the condition of a current density of 120 mA / g, and a capacity retention rate still reaching 90.66% after long-term cycling of 1000 cycles under the condition of a large current density of 600 mA / g, which is 1.3 times the capacity retention rate of Na 0.44 MnO2 under the same conditions, greatly improving the rate performance and long-cycle stability, thereby enhancing the cycle life of the sodium-ion battery. It can be used in the field of sodium-ion batteries. Description of the Drawings
[0013] Figure 1 is the XRD pattern of the positive electrode material Na 0.44 Mn 0.89 Cu 0.01 Ti 0.1 O2 obtained in Example 1;
[0014] Figure 2 is the positive electrode material Na 0.44 Mn 0.89Cu 0.01 Ti 0.1 SEM image of O2;
[0015] Figure 3 The charge and discharge curve of the sodium ion battery obtained in Example 1 (active material loading: 1.5 mg / cm 2 ; Current density: 24mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a mixed solvent of diethyl carbonate and ethylene carbonate in a ratio of 1:1 by volume);
[0016] Figure 4 This is the sodium ion battery cycle performance diagram obtained in Example 1, (active material loading: 1.5 mg / cm 2 ; Current density: 120mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a mixed solvent of diethyl carbonate and ethylene carbonate in a ratio of 1:1 by volume);
[0017] Figure 5 The positive electrode material Na obtained in Example 2 0.44 Mn 0.87 Zn 0.03 Ti 0.1 XRD pattern of O2;
[0018] Figure 6 The charge and discharge curve of the sodium ion battery obtained in Example 2 (active material loading: 1.5 mg / cm 2 ; Current density: 24mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a mixed solvent of diethyl carbonate and ethylene carbonate in a ratio of 1:1 by volume);
[0019] Figure 7 This is the sodium ion battery cycle performance diagram obtained in Example 2, (active material loading: 1.5 mg / cm 2 ; Current density: 120mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a mixed solvent of diethyl carbonate and ethylene carbonate in a ratio of 1:1 by volume);
[0020] Figure 8 The positive electrode material Na obtained in Example 3 0.44 Mn 0.85 Ca 0.05 Ti 0.1 XRD pattern of O2;
[0021] Fig. 9 The charge and discharge curve of the sodium ion battery obtained in Example 3 (active material loading: 1.5 mg / cm 2; Current density: 24mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a mixed solvent of diethyl carbonate and ethylene carbonate in a ratio of 1:1 by volume);
[0022] Fig.10 The sodium ion battery cycle performance diagram obtained in Example 3 (active material loading: 1.5 mg / cm 2 ; Current density: 120mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a 1:1 volume percentage mixed solvent of diethyl carbonate and ethylene carbonate);
[0023] Fig.11 The positive electrode material Na obtained in Example 1 0.44 XRD pattern of MnO2;
[0024] Fig.12 The charge and discharge curve of the sodium ion battery obtained in Example 1 (active material loading: 1.5 mg / cm 2 ; Current density: 24mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a mixed solvent of diethyl carbonate and ethylene carbonate in a ratio of 1:1 by volume);
[0025] Fig.13 The sodium ion battery cycle performance diagram obtained in Example 1 (active material loading: 1.5 mg / cm 2 ; Current density: 120mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a mixed solvent of diethyl carbonate and ethylene carbonate in a ratio of 1:1 by volume);
[0026] Fig.14 The sodium ion battery rate performance diagram obtained in Comparative Example 1 and Example 1 (active material loading: 1.5 mg / cm 2 ; Current density: 24mA / g, 60mA / g, 120mA / g, 360mA / g, 600mA / g, 1200mA / g, 2400mA / g, 3600mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a mixed solvent of diethyl carbonate and ethylene carbonate with a volume percentage of 1:1);
[0027] Fig.15 The cycle performance diagram of the sodium ion battery obtained in Comparative Example 1 and Example 1 (active material loading: 1.5 mg / cm 2 ; Current density: 600mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a mixed solvent of diethyl carbonate and ethylene carbonate in a ratio of 1:1 by volume).
[0028] Fig.16The positive electrode material Na obtained in Example 4 0.44 Mn 0.5 Cu 0.2 Ti 0.3 XRD pattern of O2;
[0029] Fig.17 The charge and discharge curve of the sodium ion battery obtained in Example 4 (active material loading: 1.5 mg / cm 2 ; Current density: 24mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a mixed solvent of diethyl carbonate and ethylene carbonate in a ratio of 1:1 by volume);
[0030] Fig.18 This is the sodium ion battery cycle performance diagram obtained in Example 4, (active material loading: 1.5 mg / cm 2 ; Current density: 120mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a 1:1 volume percentage mixed solvent of diethyl carbonate and ethylene carbonate);
[0031] Fig.19 The positive electrode material Na obtained in Example 5 0.44 Mn 0.3 Cu 0.3 Ti 0.4 XRD pattern of O2;
[0032] Fig. 20 The charge and discharge curve of the sodium ion battery obtained in Example 5 (active material loading: 1.5 mg / cm 2 ; Current density: 24mA / g; Electrolyte: 1.0mol / L sodium perchlorate dissolved in a mixed solvent of diethyl carbonate and ethylene carbonate in a ratio of 1:1 by volume);
[0033] Fig.21 This is the sodium ion battery cycle performance diagram obtained in Example 5, (active material loading: 1.5 mg / cm 2 ; Current density: 120 mA / g; Electrolyte: 1.0 mol / L sodium perchlorate dissolved in a 1:1 volume percentage mixed solvent of diethyl carbonate and ethylene carbonate). DETAILED DESCRIPTION
[0034] The following examples are used to verify the beneficial effects of the present invention. The purity of the sodium carbonate, manganese carbonate, copper oxide, titanium dioxide, zinc oxide, calcium oxide, organic solvent, sodium salt and metallic sodium used in each example is not less than 99%.
[0035] Example 1: This example is to prepare an air-stable high-rate long-cycle sodium ion battery cathode material Na 0.44 Mn 0.89 Cu0.01 Ti 0.1 O2, the specific preparation method is as follows: press Na 0.44 Mn 0.89 Cu 0.01 Ti 0.1 Sodium carbonate, manganese carbonate, copper oxide and titanium dioxide are weighed and mixed evenly in a stoichiometric ratio of O2, and then placed in a ball mill, 5 mL of acetone is added to every 2 g of powder, and wet ball milling is performed at 400 r / min for 12 hours to obtain a slurry; the slurry is then placed in a blast drying oven at a temperature of 120°C for 2 hours, and then ground with a mortar for 30 minutes to obtain a mixed powder; the mixed powder is then pressed into a spherical shape with a pressure of 20 MPa, placed in a muffle furnace at a temperature of 900°C for 15 hours, naturally cooled to room temperature, taken out, and manually ground into powder to obtain an air-stable high-rate long-cycle sodium ion battery positive electrode material. It is a tunnel structure oxide.
[0036] Figure 1 The tunnel structure oxide Na prepared in Example 1 0.44 Mn 0.89 Cu 0.01 Ti 0.1 XRD pattern of O2; Figure 1 It can be seen that all the diffraction peaks of this sample can be marked as typical tunnel-type Na 0.44 MnO2 structure (JCPDS card number 27-0750), which shows that Cu and Ti have been successfully doped into the tunnel-type Na 0.44 In the lattice of MnO2.
[0037] Figure 2 The tunnel structure oxide Na prepared in Example 1 0.44 Mn 0.89 Cu 0.01 Ti 0.1 SEM image of O2; Figure 2 It can be seen that the sample has a complete one-dimensional tunnel-type crystal structure.
[0038] The positive electrode of the sodium ion battery is prepared by using the air-stable high-rate long-cycle sodium ion battery positive electrode material prepared in Example 1. The specific method is as follows: 80% of the Na 0.44 Mn 0.89 Cu 0.01 Ti 0.1 O2, 10% conductive carbon black and 10% polyvinylidene fluoride; dissolve polyvinylidene fluoride powder in N-methylpyrrolidone at a concentration of 25 mg / mL to obtain a glue solution; then 0.44 Mn 0.89 Cu 0.01 Ti 0.1O2 and conductive carbon black are dispersed in the glue to obtain a slurry; the slurry is then coated on the current collector aluminum foil and placed in a vacuum drying oven at a temperature of 100°C for 12 hours to obtain the positive electrode of the sodium ion battery. 0.44 Mn 0.89 Cu 0.01 Ti 0.1 The O2 loading is 1.5 mg / cm 2 .
[0039] A sodium ion battery is prepared using a sodium ion battery positive electrode, wherein the sodium ion battery is composed of a negative electrode, a sodium ion battery positive electrode, a separator and an electrolyte; wherein the negative electrode is metallic sodium; the preparation method of the electrolyte is specifically as follows: sodium perchlorate is heated and dried in a vacuum oven at a temperature of 100°C for 6 hours to remove moisture from the sodium salt; diethyl carbonate (DEC) and ethylene carbonate (EC) are respectively subjected to reduced pressure distillation and molecular sieve drying to remove moisture; in a glove box filled with high-purity argon, 1.2244g of sodium perchlorate, 5mL of diethyl carbonate (DEC), and 5mL of ethylene carbonate (EC) are taken on an electronic balance and mixed and stirred evenly, and then allowed to stand for 12 hours to prepare an electrolyte. The concentration of sodium perchlorate in the electrolyte is 1mol / L. The separator is a glass fiber separator, which is assembled into a 2032-type button battery.
[0040] The 2032-type button battery prepared in this embodiment was subjected to a charge and discharge capacity test: a constant current charge and discharge test was performed at room temperature using a Newell-MIHW-200-160CH-B battery test system, with a test voltage range of 2.0 to 4.0 V. Figure 3 For the charge and discharge curve, Figure 3 It can be seen that under the condition of current density of 24mA / g, the first cycle discharge capacity is 104.54mAh / g, and the charge and discharge curve is smooth, which proves that there is no excessive phase change during the cycle process. The charge and discharge curves of the battery for 3 cycles completely overlap, indicating that its crystal structure has excellent cycle reversibility. Figure 4 For the cycle performance diagram, Figure 4 It can be seen that the capacity retention rate after 100 cycles at a current density of 120 mA / g is 98.5%, showing excellent cycle stability.
[0041] Example 2: This example is to prepare an air-stable high-rate long-cycle sodium ion battery cathode material Na 0.44 Mn 0.87 Zn 0.03 Ti 0.1 O2, the specific preparation method is as follows: press Na 0.44 Mn 0.87 Zn 0.03 Ti 0.1Sodium carbonate, manganese carbonate, zinc oxide and titanium dioxide are weighed and mixed evenly in a stoichiometric ratio of O2, then placed in a ball mill, acetone is added, and wet ball milling is performed at 400r / min for 12h to obtain a slurry; the slurry is then placed in a blast drying oven at a temperature of 120°C for 2h, and then ground with a mortar for 30min to obtain a mixed powder; the mixed powder is then pressed into a spherical shape with a pressure of 20MPa, placed in a muffle furnace at a temperature of 900°C for 15h, naturally cooled to room temperature, taken out, and manually ground into powder to obtain an air-stable high-rate long-cycle sodium ion battery positive electrode material. It is a tunnel structure oxide.
[0042] Figure 5 The tunnel structure oxide Na prepared in Example 2 0.44 Mn 0.87 Zn 0.03 Ti 0.1 XRD pattern of O2; Figure 5 It can be seen that all the diffraction peaks of this sample can be marked as typical tunnel-type Na 0.44 MnO2 structure (JCPDS card number 27-0750), which shows that Zn and Ti have been successfully doped into the tunnel-type Na 0.44 In the lattice of MnO2.
[0043] The positive electrode of the sodium ion battery is prepared by using the air-stable high-rate long-cycle sodium ion battery positive electrode material prepared in Example 2. The specific method is as follows: 80% of the Na 0.44 Mn 0.87 Zn 0.03 Ti 0.1 O2, 10% conductive carbon black and 10% polyvinylidene fluoride; dissolve polyvinylidene fluoride powder in N-methylpyrrolidone at a concentration of 25 mg / mL to obtain a glue solution; then 0.44 Mn 0.87 Zn 0.03 Ti 0.1 O2 and conductive carbon black are dispersed in the glue to obtain a slurry; the slurry is then coated on the current collector aluminum foil and placed in a vacuum drying oven at a temperature of 100°C for 12 hours to obtain the positive electrode of the sodium ion battery. 0.44 Mn 0.87 Zn 0.03 Ti 0.1 The O2 loading is 1.5 mg / cm 2 .
[0044] A sodium ion battery is prepared using a sodium ion battery positive electrode, wherein the sodium ion battery is composed of a negative electrode, a sodium ion battery positive electrode, a separator and an electrolyte; wherein the negative electrode is metallic sodium; the preparation method of the electrolyte is specifically as follows: sodium perchlorate is heated and dried in a vacuum oven at a temperature of 100°C for 6 hours to remove moisture from the sodium salt; diethyl carbonate (DEC) and ethylene carbonate (EC) are respectively subjected to reduced pressure distillation and molecular sieve drying to remove moisture; in a glove box filled with high-purity argon, 1.2244g of sodium perchlorate, 5mL of diethyl carbonate (DEC), and 5mL of ethylene carbonate (EC) are taken on an electronic balance and mixed and stirred evenly, and then allowed to stand for 12 hours to prepare an electrolyte. The concentration of sodium perchlorate in the electrolyte is 1mol / L. The separator is a glass fiber separator, which is assembled into a 2032-type button battery.
[0045] The 2032-type button battery prepared in this embodiment was subjected to a charge and discharge capacity test: a constant current charge and discharge test was performed at room temperature using a Newell-MIHW-200-160CH-B battery test system, with a test voltage range of 2.0 to 4.0 V. Figure 6 For the charge and discharge curve, Figure 6 It can be seen that under the condition of current density of 24mA / g, the first cycle discharge capacity is 101.92mAh / g, and the charge and discharge curve is smooth, which proves that there is no excessive phase change during the cycle. The charge and discharge curves of the battery for 3 cycles are basically overlapped, indicating that its crystal structure has excellent cycle reversibility. Figure 7 For the cycle performance diagram, Figure 7 It can be seen that the capacity retention rate after 100 cycles at a current density of 120 mA / g is 93.8%, showing excellent cycle stability.
[0046] Example 3: This example is to prepare an air-stable high-rate long-cycle sodium ion battery cathode material Na 0.44 Mn 0.85 Ca 0.05 Ti 0.1 O2, the specific preparation method is as follows: press Na 0.44 Mn 0.85 Ca 0.05 Ti 0.1Sodium carbonate, manganese carbonate, calcium oxide and titanium dioxide are weighed and mixed evenly in a stoichiometric ratio of O2, and then placed in a ball mill, 5 mL of acetone is added to every 2 g of powder, and wet ball milling is performed at 400 r / min for 12 hours to obtain a slurry; the slurry is then placed in a blast drying oven at a temperature of 120°C for 2 hours, and then ground with a mortar for 30 minutes to obtain a mixed powder; the mixed powder is then pressed into a spherical shape with a pressure of 20 MPa, placed in a muffle furnace at a temperature of 900°C for 15 hours, naturally cooled to room temperature, taken out, and manually ground into powder to obtain an air-stable high-rate long-cycle sodium ion battery positive electrode material. It is a tunnel structure oxide.
[0047] Figure 8 The tunnel structure oxide Na prepared in Example 3 0.44 Mn 0.85 Ca 0.05 Ti 0.1 XRD pattern of O2; Figure 8 It can be seen that all the diffraction peaks of this sample can be marked as typical tunnel-type Na 0.44 MnO2 structure (JCPDS card number 27-0750), which shows that Ca and Ti have been successfully doped into the tunnel-type Na 0.44 In the lattice of MnO2.
[0048] The positive electrode of the sodium ion battery is prepared by using the air-stable high-rate long-cycle sodium ion battery positive electrode material prepared in Example 3. The specific method is as follows: 80% of the Na 0.44 Mn 0.85 Ca 0.05 Ti 0.1 O2, 10% conductive carbon black and 10% polyvinylidene fluoride; polyvinylidene fluoride is dissolved in N-methylpyrrolidone at a concentration of 25 mg / mL to obtain a glue solution; then Na 0.44 Mn 0.85 Ca 0.05 Ti 0.1 O2 and conductive carbon black are dispersed in the glue to obtain a slurry; the slurry is then coated on the current collector aluminum foil and placed in a vacuum drying oven at a temperature of 100°C for 12 hours to obtain the positive electrode of the sodium ion battery. 0.44 Mn 0.85 Ca 0.05 Ti 0.1 The O2 loading is 1.5 mg / cm 2 .
[0049] A sodium ion battery is prepared using a sodium ion battery positive electrode, wherein the sodium ion battery is composed of a negative electrode, a sodium ion battery positive electrode, a separator and an electrolyte; wherein the negative electrode is metallic sodium; the preparation method of the electrolyte is specifically as follows: sodium perchlorate is heated and dried in a vacuum oven at a temperature of 100°C for 6 hours to remove moisture from the sodium salt; diethyl carbonate (DEC) and ethylene carbonate (EC) are respectively subjected to reduced pressure distillation and molecular sieve drying to remove moisture; in a glove box filled with high-purity argon, 1.2244g of sodium perchlorate, 5mL of diethyl carbonate (DEC), and 5mL of ethylene carbonate (EC) are taken on an electronic balance and mixed and stirred evenly, and then allowed to stand for 12 hours to prepare an electrolyte. The concentration of sodium perchlorate in the electrolyte is 1mol / L. The separator is a glass fiber separator, which is assembled into a 2032-type button battery.
[0050] The 2032-type button battery prepared in this embodiment was subjected to a charge and discharge capacity test: a constant current charge and discharge test was performed at room temperature using a Newell-MIHW-200-160CH-B battery test system, with a test voltage range of 2.0 to 4.0 V. Fig. 9 For the charge and discharge curve, Fig. 9 It can be seen that under the condition of current density of 24mA / g, the first cycle discharge capacity is 94.27mAh / g, and the charge and discharge curve is smooth, which proves that there is no excessive phase change during the cycle process. The charge and discharge curves of the battery for 3 cycles completely overlap, indicating that its crystal structure has excellent cycle reversibility. Fig.10 For the cycle performance diagram, Fig.10 It can be seen that the capacity retention rate after 100 cycles at a current density of 120 mA / g is 93.4%, showing excellent cycle stability.
[0051] Comparative Example 1: This example is to prepare a tunnel structure oxide Na 0.44 MnO2, the specific preparation method is as follows: press Na 0.44 Sodium carbonate and manganese carbonate were weighed and mixed evenly in a ball mill. 5 mL of acetone was added to every 2 g of powder. The wet ball milling was carried out at 400 r / min for 12 h. The product was dried in a blast drying oven at 120 ° C for 2 h, and then ground in a mortar for 30 min. The powder was then pressed into a spherical shape at a pressure of 20 MPa, placed in a muffle furnace and calcined at 900 ° C for 15 h, naturally cooled to room temperature, taken out, and ground manually to obtain Na 0.44 MnO2.
[0052] Fig.11 The tunnel structure oxide Na prepared in Comparative Example 1 0.44 XRD pattern of MnO2; Fig.11It can be seen that all the diffraction peaks of this sample can be marked as typical tunnel-type Na 0.44 MnO2 structure (JCPDS card number 27-0750), without impurity phase, indicating the successful synthesis of single-phase tunnel-type Na 0.44 MnO2.
[0053] Using Na prepared in Comparative Example 1 0.44 The positive electrode of sodium ion battery is prepared by MnO2. The specific method is as follows: 80% of Na 0.44 MnO2, 10% conductive carbon black and 10% polyvinylidene fluoride; polyvinylidene fluoride is dissolved in N-methylpyrrolidone at a concentration of 25 mg / mL to obtain a glue; then Na 0.44 MnO2 and conductive carbon black are dispersed in the glue to obtain a slurry; the slurry is then coated on the current collector aluminum foil and placed in a vacuum drying oven at a temperature of 100°C for 12 hours to obtain the positive electrode of the sodium ion battery. 0.44 The loading of MnO2 is 1.5 mg / cm 2 .
[0054] A sodium ion battery is prepared using a sodium ion battery positive electrode, wherein the sodium ion battery is composed of a negative electrode, a sodium ion battery positive electrode, a separator and an electrolyte; wherein the negative electrode is metallic sodium; the preparation method of the electrolyte is specifically as follows: sodium perchlorate is heated and dried in a vacuum oven at a temperature of 100°C for 6 hours to remove moisture from the sodium salt; diethyl carbonate (DEC) and ethylene carbonate (EC) are respectively subjected to reduced pressure distillation and molecular sieve drying to remove moisture; in a glove box filled with high-purity argon, 1.2244g of sodium perchlorate, 5mL of diethyl carbonate (DEC), and 5mL of ethylene carbonate (EC) are taken on an electronic balance and mixed and stirred evenly, and then allowed to stand for 12 hours to prepare an electrolyte. The concentration of sodium perchlorate in the electrolyte is 1mol / L. The separator is a glass fiber separator, which is assembled into a 2032-type button battery.
[0055] The 2032-type button battery prepared in this comparative example was subjected to a charge and discharge capacity test: at room temperature, a constant current charge and discharge test was performed using a Newell-MIHW-200-160CH-B battery test system, with a test voltage range of 2.0 to 4.0 V. Fig.12 For the charge and discharge curve, Fig.12 It can be seen that under the condition of current density of 24mA / g, the first cycle discharge capacity is 107.92mAh / g, and there are 6 platforms in the charge and discharge curve of the battery, indicating that too many phase changes occur during the cycle process, and the charge and discharge curves of the battery for 3 cycles do not overlap. With the increase of the number of cycles, the discharge capacity gradually decreases, indicating that the irreversible phase change occurring during the charge and discharge process leads to poor cycle reversibility. Fig.13 For the cycle performance diagram, Fig.13 It can be seen that the capacity retention rate after 100 cycles at a current density of 120 mA / g is only 91.3%.
[0056] Fig.14 It is a comparison chart of the rate performance of the sodium ion batteries obtained in Comparative Example 1 and Example 1. Under the conditions of current density of 24mA / g, 60mA / g, 120mA / g, 360mA / g, 600mA / g, 1200mA / g, 2400mA / g and 3600mA / g, the rate performance of Example 1 is better than that of Comparative Example 1, especially at high current density, the performance improvement of Example 1 is more obvious.
[0057] Fig.15 It is a comparison chart of the cycle performance of the sodium ion batteries obtained in Comparative Example 1 and Example 1. Under the condition of a high current density of 600 mA / g, the capacity retention rate of the material in Comparative Example 1 after a long cycle of 1000 cycles is 70.6%, and the capacity retention rate of the material prepared in Example 1 after a long cycle of 1000 cycles can still reach 90.66%, which is about 1.3 times the capacity retention rate of Comparative Example 1 under the same conditions.
[0058] Example 4: This example is to prepare an air-stable high-rate long-cycle sodium ion battery cathode material Na 0.44 Mn 0.5 Cu 0.2 Ti 0.3 O2, the specific preparation method is as follows: press Na 0.44 Mn 0.5 Cu 0.2 Ti 0.3 Sodium carbonate, manganese carbonate, copper oxide and titanium dioxide are weighed and mixed evenly in a stoichiometric ratio of O2, and then placed in a ball mill, 5 mL of acetone is added to every 2 g of powder, and ball milled at 400 r / min for 12 hours to obtain a slurry; the slurry is then placed in a blast drying oven at a temperature of 120°C for 2 hours, and then ground with a mortar for 30 minutes to obtain a mixed powder; the mixed powder is then pressed into a spherical shape with a pressure of 20 MPa, placed in a muffle furnace at a temperature of 900°C for 15 hours, naturally cooled to room temperature, taken out, and manually ground into powder to obtain an air-stable high-rate long-cycle sodium ion battery positive electrode material. It is a tunnel structure oxide.
[0059] Fig.16 The tunnel structure oxide Na prepared in Example 4 0.44 Mn 0.5 Cu 0.2 Ti 0.3 XRD pattern of O2; Fig.16It can be seen that all the diffraction peaks of this sample can be marked as typical tunnel-type Na 0.44 MnO2 structure (JCPDS card number 27-0750), which shows that Cu and Ti have been successfully doped into the tunnel-type Na 0.44 In the lattice of MnO2.
[0060] The positive electrode of the sodium ion battery is prepared by using the air-stable high-rate long-cycle sodium ion battery positive electrode material prepared in Example 4. The specific method is as follows: 80% of the Na 0.44 Mn 0.5 Cu 0.2 Ti 0.3 O2, 10% conductive carbon black and 10% polyvinylidene fluoride; polyvinylidene fluoride is dissolved in N-methylpyrrolidone at a concentration of 25 mg / mL to obtain a glue solution; then Na 0.44 Mn 0.5 Cu 0.2 Ti 0.3 O2 and conductive carbon black are dispersed in the glue to obtain a slurry; the slurry is then coated on the current collector aluminum foil and placed in a vacuum drying oven at a temperature of 100°C for 12 hours to obtain the positive electrode of the sodium ion battery. 0.44 Mn 0.5 Cu 0.2 Ti 0.3 The O2 loading is 1.5 mg / cm 2 .
[0061] A sodium ion battery is prepared using a sodium ion battery positive electrode, wherein the sodium ion battery is composed of a negative electrode, a sodium ion battery positive electrode, a separator and an electrolyte; wherein the negative electrode is metallic sodium; the preparation method of the electrolyte is specifically as follows: sodium perchlorate is heated and dried in a vacuum oven at a temperature of 100°C for 6 hours to remove moisture from the sodium salt; diethyl carbonate (DEC) and ethylene carbonate (EC) are respectively subjected to reduced pressure distillation and molecular sieve drying to remove moisture; in a glove box filled with high-purity argon, 1.2244g of sodium perchlorate, 5mL of diethyl carbonate (DEC), and 5mL of ethylene carbonate (EC) are taken on an electronic balance and mixed and stirred evenly, and then allowed to stand for 12 hours to prepare an electrolyte. The concentration of sodium perchlorate in the electrolyte is 1mol / L. The separator is a glass fiber separator, which is assembled into a 2032-type button battery.
[0062] The 2032-type button battery prepared in this embodiment was subjected to a charge and discharge capacity test: a constant current charge and discharge test was performed at room temperature using a Newell-MIHW-200-160CH-B battery test system, with a test voltage range of 2.0 to 4.0 V. Fig.17 For the charge and discharge curve, Fig.17It can be seen that under the condition of current density of 24mA / g, the first cycle discharge capacity is 102.83mAh / g, and the charge and discharge curve is smooth, which proves that there is no excessive phase change during the cycle. The charge and discharge curves of the battery for 3 cycles completely overlap, indicating that its crystal structure has excellent cycle reversibility. Fig.18 For the cycle performance diagram, Fig.18 It can be seen that the capacity retention rate after 100 cycles at a current density of 120 mA / g is 97.6%, showing excellent cycle stability.
[0063] Example 5: This example is to prepare an air-stable high-rate long-cycle sodium ion battery cathode material Na 0.44 Mn 0.3 Cu 0.3 Ti 0.4 O2, the specific preparation method is as follows: press Na 0.44 Mn 0.3 Cu 0.3 Ti 0.4 Sodium carbonate, manganese carbonate, copper oxide and titanium dioxide are weighed and mixed evenly in a stoichiometric ratio of O2, and then placed in a ball mill, 5 mL of acetone is added to every 2 g of powder, and ball milled at 400 r / min for 12 hours to obtain a slurry; the slurry is then placed in a blast drying oven at a temperature of 120°C for 2 hours, and then ground with a mortar for 30 minutes to obtain a mixed powder; the mixed powder is then pressed into a spherical shape with a pressure of 20 MPa, placed in a muffle furnace at a temperature of 900°C for 15 hours, naturally cooled to room temperature, taken out, and manually ground into powder to obtain an air-stable high-rate long-cycle sodium ion battery positive electrode material. It is a tunnel structure oxide.
[0064] Fig.19 The tunnel structure oxide Na prepared in Example 5 0.44 Mn 0.3 Cu 0.3 Ti 0.4 XRD pattern of O2; Fig.19 It can be seen that all the diffraction peaks of this sample can be marked as typical tunnel-type Na 0.44 MnO2 structure (JCPDS card number 27-0750), which shows that Cu and Ti have been successfully doped into the tunnel-type Na 0.44 In the lattice of MnO2.
[0065] The positive electrode of the sodium ion battery is prepared by using the air-stable high-rate long-cycle sodium ion battery positive electrode material prepared in Example 5. The specific method is as follows: 80% of the Na 0.44 Mn 0.3 Cu 0.3 Ti 0.4O2, 10% conductive carbon black and 10% polyvinylidene fluoride; polyvinylidene fluoride is dissolved in N-methylpyrrolidone at a concentration of 25 mg / mL to obtain a glue solution; then Na 0.44 Mn 0.3 Cu 0.3 Ti 0.4 O2 and conductive carbon black are dispersed in the glue to obtain a slurry; the slurry is then coated on the current collector aluminum foil and placed in a vacuum drying oven at a temperature of 100°C for 12 hours to obtain the positive electrode of the sodium ion battery. 0.44 Mn 0.3 Cu 0.3 Ti 0.4 The O2 loading is 1.5 mg / cm 2 .
[0066] A sodium ion battery is prepared using a sodium ion battery positive electrode, wherein the sodium ion battery is composed of a negative electrode, a sodium ion battery positive electrode, a separator and an electrolyte; wherein the negative electrode is metallic sodium; the preparation method of the electrolyte is specifically as follows: sodium perchlorate is heated and dried in a vacuum oven at a temperature of 100°C for 6 hours to remove moisture from the sodium salt; diethyl carbonate (DEC) and ethylene carbonate (EC) are respectively subjected to reduced pressure distillation and molecular sieve drying to remove moisture; in a glove box filled with high-purity argon, 1.2244g of sodium perchlorate, 5mL of diethyl carbonate (DEC), and 5mL of ethylene carbonate (EC) are taken on an electronic balance and mixed and stirred evenly, and then allowed to stand for 12 hours to prepare an electrolyte. The concentration of sodium perchlorate in the electrolyte is 1mol / L. The separator is a glass fiber separator, which is assembled into a 2032-type button battery.
[0067] The 2032-type button battery prepared in this embodiment was subjected to a charge and discharge capacity test: a constant current charge and discharge test was performed at room temperature using a Newell-MIHW-200-160CH-B battery test system, with a test voltage range of 2.0 to 4.0 V. Fig. 20 For the charge and discharge curve, Fig. 20 It can be seen that under the condition of current density of 24mA / g, the first cycle discharge capacity is 92.53mAh / g, and the charge and discharge curve is smooth, which proves that there is no excessive phase change during the cycle process. The charge and discharge curves of the battery for 3 cycles completely overlap, indicating that its crystal structure has excellent cycle reversibility. Fig.21 For the cycle performance diagram, Fig.21 It can be seen that the capacity retention rate after 100 cycles at a current density of 120 mA / g is 93.1%, showing excellent cycle stability.
Claims
1. An air-stable high-rate long-cycle sodium ion battery cathode material, characterized in that The molecular formula of this material is Na a Mn 1-x-y TM x Ti y O2, where TM is one or more of K, Al, Ca, Cu, Zn, 0.22≤a≤0.66, 0 <x≤0.30,0<y≤0.56。 2. A method for preparing an air-stable high-rate long-cycle sodium ion battery positive electrode material according to claim 1, characterized in that: The specific method is as follows: Weigh sodium carbonate, manganese carbonate, the corresponding oxide or carbonate of TM, and titanium dioxide according to the stoichiometric ratio of the cathode material Na a Mn 1-x-y TM x Ti y O2, and mix them evenly to obtain a mixture; where TM in Na a Mn 1-x-y TM x Ti y O2 is one or more of K, Al, Ca, Cu, Zn, 0.22 ≤ a ≤ 0.66, 0 < x ≤ 0.30, 0 < y ≤ 0.56; then place the mixture in a ball milling jar, add acetone, and ball mill it for 2 - 24 h under the condition of 200 - 800 r / min to obtain a slurry; then place the slurry in a blast drying oven and dry it for 1 - 12 h at a temperature of 80 - 150 °C, and then grind it with a mortar for 10 - 60 min to obtain a mixed powder; subsequently, press the mixed powder into a sphere under a pressure of 15 - 25 MPa, place it in a muffle furnace at a temperature of 800 - 1050 °C and bake it for 8 - 20 h, take it out after natural cooling to room temperature, and grind it into powder to obtain a high-rate long-cycle sodium-ion battery cathode material with air stability.
3. The use of an air-stable high-rate long-cycle sodium ion battery positive electrode material according to claim 1, characterized in that This application is to use air-stable high-rate and long-cycle sodium-ion battery positive electrode materials to prepare the positive electrode of the sodium-ion battery.
4. The use of an air-stable high-rate long-cycle sodium ion battery positive electrode material according to claim 3, characterized in that: The method for preparing a positive electrode by using an air-stable high-rate long-cycle sodium ion battery positive electrode material is carried out according to the following steps: 20% to 95% of the air-stable high-rate long-cycle sodium ion battery positive electrode material, 2% to 40% of conductive carbon black and 3% to 40% of polyvinylidene fluoride are weighed by mass percentage; polyvinylidene fluoride is dissolved in N-methylpyrrolidone to obtain a glue solution; the air-stable high-rate long-cycle sodium ion battery positive electrode material and the conductive carbon black are dispersed in the glue solution to obtain a slurry; the slurry is coated on a current collector and dried to obtain a sodium ion battery positive electrode.
5. The use of an air-stable high-rate long-cycle sodium ion battery positive electrode material according to claim 4, characterized in that: Air-stable high-rate and long-cycle sodium-ion battery cathode materials with a loading of 0.5 to 10 mg / cm 2 .
6. The use of an air-stable high-rate long-cycle sodium ion battery positive electrode material according to claim 3, characterized in that: The sodium ion battery assembled by using the sodium ion battery positive electrode is composed of a negative electrode, a sodium ion battery positive electrode, a separator and an electrolyte; wherein the negative electrode is metallic sodium; the electrolyte is composed of an organic solvent and a sodium salt; the organic solvent is one of ethylene carbonate, fluorinated ethylene carbonate, diethyl carbonate, dimethyl carbonate and propylene carbonate or a combination of several thereof; the sodium salt is one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, sodium fluoride and sodium difluorooxalatoborate or a combination of several thereof; and the concentration of the sodium salt in the electrolyte is 0.1 mol / L to 10 mol / L.
7. The use of an air-stable high-rate long-cycle sodium ion battery positive electrode material according to claim 6, characterized in that: The preparation method of the electrolyte is as follows: heating and drying the sodium salt in a vacuum oven to remove moisture from the sodium salt; distilling the organic solvent under reduced pressure and drying it with a molecular sieve to remove moisture; and then fully mixing the sodium salt and the organic solvent to obtain the electrolyte.
Citation Information
Patent Citations
Sodium ion secondary battery, active substance, positive electrode and negative electrode used by sodium ion secondary battery, and preparation method of active substance
CN103579605A
Aqueous-solution sodium-ion battery and cathode material, preparation method and application thereof
CN104795555A
Cathode material for water-based rechargeable sodium battery and corresponding sodium battery
CN106328917A
High-capacity sodium ion battery positive electrode material
CN111864200A
P2 type layered sodium ion battery positive electrode material and preparation method thereof
CN113921809A